Intertextuality in William Shakespeare’s Drama Antony and Cleopatra - Rahmawati, Eri; Handayani, Rita (Journal of Linguistics, Literacy, and Pedagogy, 2024)
The aim of this research is to reveal the intertextuality of Antony and Cleopatra play by William Shakespeare. To reach the goal, this research utilizes intertextuality theory from Julia Kristeva. This research is library research and descriptive qualitative research. The result of this study points out that Shakespeare’s drama Antony and Cleopatra was written based on real events in Rome history. Intertextuality aspect of this drama is found in the resemblance between the character names and events in the drama with the history of Rome written by Plutarch Lives of the Roman Empire and the Lives of Caesars. Shakespeare got the inspiration from the history of Rome by Plutarch for the background of history, plot and intimate detail of the affair between Roman General Antony and Egypt Queen Cleopatra. In fact, the description of Cleopatra upon her vessel presented by the character Enobarbus in the play (Act II, Scene ii, 190-225) is nearly a word for word translation of a passage from Plutarch.